PREPARING STUDENTS FOR PROFESSIONAL ACTIVITY IN LESSONS WITH THE HELP OF USING CLIL TECHNOLOGY - Tuxtayeva Nilufar Achilovna (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
In recent years, the integration of innovative teaching methods in higher education has become a key factor in improving the quality of professional training. One of the most effective pedagogical approaches is the CLIL (Content and Language Integrated Learning) methodology, which combines the learning of subject-specific content with the development of foreign language competence. This article discusses the importance of applying CLIL technology in preparing students for professional activity, its pedagogical advantages, and its contribution to the formation of globally competitive specialists.